News Writing for Television and Radio - Ricky Telg; Lisa Lundy (EDIS)
This publication on news writing television and radio is the fourth of a five-part series on news media writing. This series also covers an introduction to news media writing, news writing for print, grammar and punctuation, and interviews for news stories. Minor revision by Ricky Telg and Lisa Lundy. Published by the UF/IFAS Department of Agricultural Education and Communication. 4pp.